Introduction and executive summary for the supplement micronutrients in Latin America: Current state and research - Soto-Méndez, María J.; Boy, Erick (SAGE Publications, 2024)
Global health and nutrition stakeholders are facing a period full of changes and challenges, especially in low- and middle-income countries (LMIC). Almost every country is experiencing at least, one burden of malnutrition,1 and among them many are facing the triple burden of malnutrition, both associated with unhealthy and nondiverse diets and reduced physical activity. According to the State of Food Security and Nutrition in the World Report, in 2022, between 691 and 783 million people faced chronic hunger, representing an increase of 122 million people compared to 2019. It also informed that 3.1 billion people could not afford a healthy diet.2 On the one hand, economic shocks, war, violence, and climate-related disruptions are the leading causes of the current steep increase in the global burden of hunger in all its forms. The COVID-19 pandemic and other repeated pandemic shocks further reduce food and nutrition security of poor countries.3 On the other hand, chronic noncommunicable diseases, most of which are associated with overweight-obesity and unhealthy behavioral and environmental risk factors, continue to rise as the principal causes of death and disability worldwide, also disproportionately impacting LMIC.4 While the prevalence of hunger in Latin America and the Caribbean (LAC) is lower than the global average, food insecurity affects a higher proportion of the population in the region (40%) relative to the global prevalence (29.3%). The region also experiences the highest cost of a healthy diet, with 131 million people unable to afford to meet the recommended nutritional requirements that healthy diets would provide.5-7 Consequently, the risks of nutrient deficiency and excess for the region can be inferred, but the scarcity of current nationally representative data on micronutrient deficiencies is neither useful for program planning or evaluation nor conducive to narrowing the equity and justice gaps in the region.